NURSING ROLE IN PROMOTING THE MENTAL HEALTH OF ADOLESCENTS WITH ANXIETY DISORDERS (REMUNOM, 2024)
Adolescent anxiety disorder is a growing mental health concern, with significant impacts on the lives of young people. Nursing plays a fundamental role in promoting mental well-being and managing this disorder, adopting an integrated approach that combines pharmacological and non-pharmacological interventions. This activity plays an important role in the education and guidance of adolescents and their families. Nurses should provide information about the signs and symptoms of anxiety, highlight the importance of multidisciplinary treatment and encourage the search for professional support during times of crisis. The person-centered approach is a fundamental characteristic of mental health nursing practice. Nurses recognize each adolescent's individuality and work collaboratively with them to develop personalized care plans that meet their specific needs. This includes promoting healthy coping strategies, strengthening self-esteem, and establishing therapeutic bonds that promote emotional well-being and resilience. This study was carried out through a literature review. This research enables nursing professionals to develop strategies that meet the real mental health needs of adolescents, which are often neglected due to their lower frequency in health services.